The Mayan Pope and His Competition: Local, National and Transnational Representations of the 2012 Phenomenon - MacKenzie, C. James (Anthropologica, 2015)
This article reviews media coverage of the much hyped end of a cycle in the Maya long count calendar in December 2012, focusing on the efforts of différent indigenous and non-indigenous agents in Guatemala and beyond to claim its meaning. I note a convergence between Maya and New Age interpretations of the transcendental significance of the date, though I argue that the relevance of boundaries between Maya and others varied in terms of the positioning (local, national and transnational) of key players. This highlights challenges facing practitioners of contemporary Maya spirituality as it enters transnational circuits, particularly in terms of establishing religious authority.